Robust of Low Rank Matrix and Collaborative Representation for Face Recognition (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we have introduced improvement Robustness method for facerecognition, which combine of the low-rank with collaborative representation. Theapplications of this model are based on the truth that proposed method can effectively dealwith the face recognition across different illumination and occlusion, as well as the nature ofcorrupted and occluded regions. The method is able to be applied directly on original faceimage neither does it require feature selection, nor does it need many training samples.Experiments have been performed on various benchmark face database. The proposed methodoutperforms many state-of-the-art methods.